Evaluating the illumination performance of LED fishing lamps with different configurations in Pacific saury fishery - Fei Li; Chuanxiang Hua; Qingcheng Zhu (PLoS ONE, 2025)
The configurations of artificial light on fishing vessels are important factors that affect underwater lighting characteristics, fish behavior, and catch efficiency in light fishery. A validated illumination model was used to investigate the illumination performances among three different shapes and mounting modes of commercial light-emitting diode (LED) fishing devices installed at angles of 45°, 60°, and 75°, respectively. The results showed that the illumination distributions of all these differently shaped or mounted LED modules exhibited a series of concentric iso-illuminance curves, but significant differences were found in the detailed lighting performances of the modules with different allocations. With increasing angle, the illuminance differences among the three types of LED modules decreased, and the deviations in the illumination distributions at different angles were mainly concentrated around the light source. Notably, at the same angle, the maximum illuminance value of a rectangular vertically mounted lamp (RVL) was always higher than those of the other two kinds of modules. The findings indicated that the LED fishing lamps manufactured into rectangular shape and mounted vertically at installation angles of 60° to 75° had superior effects in attracting saury.